The Role of Financial Digitalization in Eradicating Corruption in Indonesia - Rabith Madah Khulaili Harsya; Badruddin Nasir; Fadil Mas’ud; Robert A. Serang; Iwan Harsono (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
Technological advances provide a number of benefits in various sectors, one of which is the financial sector. Technological advances in the financial sector or commonly known as financial digitalization have made data bookkeeping more effective, easily accessible, transparent, and made it easier for employees to carry out financial reports. Based on this, this research aims to analyze the role of financial digitalization in preventing corruption in Indonesia. This research is qualitative research with a descriptive approach, namely describing the meaning of technology, technological developments, the benefits of technology, its relationship with finance, and the benefits of digitalization of technology in preventing corruption in Indonesia. The data used by researchers in this article is secondary data, namely in the form of legislation, scientific articles, books, websites and other things that are usually used in every research. The researchers analyzed these data using the stages of data collection analysis, data reduction, data analysis, and drawing Conclusion. The result in this research show that the presence of financial digitalization at least has benefits in preventing corruption because of its transparency. With the digitalization of financial tenders, financial reporting, and other things that are transparent and do not endanger privacy, they can be accessed easily by all stake holders, supervisors, partner companies, internal company parties, and so on to find out the tender winner, continuity of the tender, until completion of the tender. Apart from that, if suspicious potential for corruption is found, it can be tracked easily. Because of this, anyone who has the intention to commit corruption will be discouraged.